Conceptualizing Reading in the Qur’an: A Thematic (Maudhu‘i) Tafsīr Analysis: The Lexical Spectrum and Semantic Hierarchy of Reading in the Qur’an Objects, Subjects, and Methodologies of Reading: An Ontological and Epistemological Analysis The Synthesis of a Conceptual Model: Integral Reading as a Qur’anic Epistemology - Muhammad Diaz Supandi; M. Bili Syaputra; Ahnaf Falih; Muhammad Faid Ghathfan Haryudha; Alfan Arif Rabbani; Mahmud Rifaannudin (Yayasan Pendidikan Tanggui Baimbaian, 2026)
This study aims to reconstruct the conceptualization of reading in the Qur’an, which is often reduced to mere technical literacy, while the sacred text offers a holistic-integrative paradigm. Departing from the problem of fragmentation in previous studies that are partial and have not touched the semantic integrity of key lexical networks (qara’a, tala, darasa, etc.), this research addresses the urgency of theoretical-practical needs to formulate a coherent Qur’anic epistemology of reading as a foundation for Islamic philosophy of science and education. Using a rigorous thematic ( maudhu’i ) tafsir method, an exhaustive thematic exploration of all related verses, semantic-contextual analysis, and synthesis of a conceptual model were conducted. The novelty of the research lies in three aspects: the application of rigorous maudhu’i procedures for complex themes, comparative-interconnective semantic analysis between lexicons, and the construction of a theory in the form of a Multilayered Epistemology of Qur’anic Reading Model (Technical-Procedural, Performative-Reflective, and Contemplative-Constructive Layers). The results indicate that reading in the Qur’an is an active, hierarchical epistemology with dual objects ( qauliyah and kauniyah verses), an ideal subject ( ulul albab ), and an integrative-dialogical methodology, aiming to produce beneficial knowledge ( ‘ilm nāfi’ ) and universal benefit ( rahmatan lil ‘ālamīn ). This model serves as an operational framework for revitalizing an integrated Islamic knowledge paradigm.